Manifestation of Character Education in Ponorogo Keling Dance and Its Relevance as Teaching Material - Pramudiyanto, Ahmad; Sari, Fitriana Kartika; Melandika, Ardonna (Jurnal Paedagogy, 2024)
The study aims to identify character education values in the Ponorogo Keling Dance. The character education values identified were assessed for their relevance as teaching material for the Javanese language subject for secondary-level students. The approach used in this research was qualitative with a constructivist paradigm. The data collection techniques were observation, interviews, literature study, and documentation. The resource person in this research was Wiyoto, head of the Guno Joyo Studio, Keling Dance Association. Data in terms of symbols and meaning will be analyzed using the hypersemiotic theory. The data validity used triangulation of data sources. The results showed that the Keling dance had local wisdom values indicated in symbols. These symbols were visualized in the Keling dance choreography and characters. After employing hyper semiotic theory, the study found symbols in the Keling dance containing character education values. These values are tolerance, creativity, national spirit, love of the nation, and care for the environment. These values are relevant to teaching material for the Javanese language subject in terms of character education values, availability to be integrated with the Javanese language subject, and contextuality following local cultural characteristics. The use of the Keling Dance as teaching material for the Javanese language subject hopefully introduces native Ponorogo arts other than reog.